Sport-Related Concussion Alters Indices of Dynamic Cerebral Autoregulation - Wright, Alexander D.; Smirl, Jonathan D.; Bryk, Kelsey; Fraser, Sarah; Jakovac, Michael; van Donkelaar, Paul (Frontiers in Neurology, 2018)
Sport-related concussion is known to affect a variety of brain functions. However, the impact of this brain injury on cerebral autoregulation is poorly understood. Thus, the goal of the current study was to determine the acute and cumulative effects of sport-related concussion on indices of dynamic cerebral autoregulation. Towards this end, 179 elite, junior-level (age 19.6 ± 1.5 years) contact sport (ice hockey, American football) athletes recruited for pre-season testing, 42 with zero prior concussions and 31 with three or more previous concussions. Eighteen athletes sustained a concussion during that competitive season, and completed follow-up testing at 72-hours, 2-weeks, and 1-month post-injury. Beat-by-beat arterial blood pressure (BP) and middle cerebral artery blood velocity (MCAv) were recorded using finger photoplethysmography and transcranial Doppler ultrasound, respectively. Five minutes of repetitive squat-stand manoeuvres induced BP oscillations at 0.05 Hz and 0.10 Hz (20-s and 10-s cycles, respectively). The BP-MCAv relationship was quantified using transfer function analysis to estimate Coherence (correlation), Gain (amplitude ratio), and Phase (timing offset). At a group level, repeated-measures ANOVA indicated 0.10 Hz Phase was significantly reduced following an acute concussion, compared to preseason, by 23% (-0.136 ± 0.033 rads) at 72 hours and by 18% (-0.105 ± 0.029 rads) at 2-weeks post-injury, indicating impaired autoregulatory functioning; recovery to preseason values occurred by 1-month. Athletes were cleared to return to competition after a median of 14 days (range 7-35), implying physiologic dysfunction persisted beyond clinical recovery in many cases. When comparing dynamic pressure buffering between athletes with zero prior concussions and those with three or more, no differences were observed. Sustaining an acute sport-related concussion induces transient impairments in the capabilities of the cerebrovascular pressure-buffering system that may persist beyond two weeks, and may be due to a period of autonomic dysregulation. Athletes with a history of three or more concussions did not exhibit impairments relative to those with zero prior concussions, suggesting recovery of function over time. Findings from this study support the potential need to consider physiological recovery in deciding when patients should return-to-play following a concussion.